LINC00941 Promotes Progression of Non-Small Cell Lung Cancer by Sponging miR-877-3p to Regulate VEGFA Expression - Ren, Min-Huan; Chen, Si; Wang, Liang-Ge; Rui, Wen-Xiu; Li, Pei (Frontiers in Oncology, 2021)
Long noncoding RNAs (lncRNAs) play critical roles in carcinoma occurrence and metastasis. LINC00941 has been found to mediate the development of gastric cancer, and LINC00941 was negatively associated with the longer overall survival of lung adenocarcinoma patients. Herein, our aim was to investigate the effects and mechanisms of LINC00941 in NSCLC progression. Microarray was used to identify the change lncRNAs in NSCLC, LINC00941 was found to increase in tumor tissues and patients’ plasma. Knockdown of LINC00941 didn’t modulate the proliferation of NSCLC cells, but inhibition of LINC00941 in NSCLC cells suppressed the angiogenesis ability of human umbilical vein endothelial cells (HUVECs). Moreover, LINC00941 promoted tumorigenesis in vivo, while si-LINC00941 inhibited tumor development of NSCLC. VEGFA was should to be significantly modulated by LINC00941 in NSCLC cells, then luciferase assay proved that LINC00941 regulated VEGFA expression via interacting with miR-877-3p. Followed functional experiments indicated that overexpression of LINC00941 accelerated angiogenesis and NSCLC tumor progression via miR-877-3p/VEGFA axis both in vitro and in vivo. In conclusion, our results clarified the LINC00941 function for the first time, and LINC00941 promoted the progression of NSCLC, which was mediated by miR-877-3p/VEGFA axis. This study might provide new understanding and targets for NSCLC diagnosis and treatment.